Subjective life expectancy in transition: a longitudinal study of Korean baby boomers - Ho, Jeong Hwa (Asian Population Studies, 2021)
Subjective life expectancy predicts actual mortality and provides individual timeframes. This four-year longitudinal study on Korean baby boomers in middle age examines how subjective life expectancy changes as people get older and how changes in health and socioeconomic status cause these shifts. Compared to population-based actuarial life expectancies, men in their fifties overestimated their future longevity by 1.2 years and women underestimated by 4.1 years. Subjective life expectancy increased as the baby boomers aged. The fixed effects regression analyses showed that subjective longevity changed along with known health and mortality factors. An increase in socioeconomic resources predicted an increase in subjective life expectancy, while smoking or health deterioration led to decrease. Generally, baby boomers form rational expectations on their future longevity based on established correlates of health and mortality. However, women’s underestimation of life expectancy warrants social concern on longevity risk.
Keywords: baby boomers; health behaviour; health status; Korea; socioeconomic resource; Subjective life expectancy